British interest rate convergence between the US and Europe: A recursive cointegration analysis - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper addresses the question of the British state of convergence towards the Euro area, compared to the USA. Economically, the analysis is based on dependences in the money and capital markets, namely the uncovered interest parity (UIP) and the expectation hypothesis of the term structure (EHT), The econometric procedure consists of backward recursive calculations carried out in a cointegration framework. As the ecidence for the single parities remains unconvincing, UIP and EHT are combined in a common model. Generally, the results are in favour of a growing British integration into the European Currency Union.
Keywords: E43; E44; C32; 330; Nominal Convergence; Cointegration; UIP; Term Structure; Euro Area